Undergraduate occupational therapy students’ perceptions of their preparedness for splinting in hand rehabilitation: An exploratory study at the University of KwaZulu-Natal - Sizophila Gwala; Nompumelelo Mtshali; Sithembile Nene; Casey Stanley; Luther Lebogang Monareng (PLoS ONE, 2026)
Background Hand rehabilitation, particularly splinting, is a key area in occupational therapy. However, existing literature suggests that students often feel inadequately prepared, particularly concerning splinting in hand rehabilitation. This highlights the need for further research and improvements. This research explored the perceptions held by undergraduate occupational therapy students regarding splinting in hand rehabilitation at the University of KwaZulu-Natal, with the aim of informing curriculum improvements. The novelty of this study lies in its focus on the University of KwaZulu-Natal, providing institution-specific insights that are currently underexplored in the literature, using Kolb’s Experiential Learning Theory, to contextualise this study. Methods This qualitative study gathered data from 3 rd and 4 th year occupational therapy students at the University of KwaZulu-Natal using purposive sampling. The Consolidated Criteria for Reporting Qualitative Research (COREQ): a 32-item checklist for interviews and focus groups was followed. The data were collected through semi-structured interviews using a piloted question guide and thematic analysis was used to analyse the data. Ethical clearance was received for this research. Results This research comprised 16 participants: n = 5 males and n = 11 females, all of whom were undergraduates. The number of physical clinical fieldwork blocks completed by the participants ranged from two to three. The number of splints made during these blocks ranged from no splints to four or more. Four distinctive themes emerged: student readiness and preparedness, challenges in splinting, comparison of readiness in 3 rd and 4 th year, and suggested solutions to bridge the gaps. Conclusion Despite acquiring theoretical knowledge, students felt underprepared and uncertain due to limited clinical opportunities, inadequate supervision, and minimal hands-on practice during fieldwork. This lack of confidence and competence may deter students from pursuing specialisation in hand rehabilitation. To address these gaps, students recommended strategies such as increasing practical time dedicated to splinting, introducing training earlier in the program, expanding the splinting curriculum to cover a broader range of splint types, and strengthening university support structures, which align with existing literature, that emphasises the crucial role of hands-on experience in fostering confidence and competence. These findings have implications for curriculum development and suggest the need for policy reforms prioritising clinical competency in undergraduate occupational therapy education.